The Influence of Facilities And Service Quality on Customer Satisfaction at Mercure Serpong Alam Sutera Hotel - Kusumaningrum, Anisa Putri; Pradini, Gagih; Prawiraharja, Ananto (CV ODIS, 2023)
Hotels today are facing increasing competition in the hospitality industry, so it is important to understand the factors that affect customer satisfaction. Based on one To determine the effect of facilities on customer satisfaction at Mercure Serpong Alam Sutera Hotel, to determine the effect of service quality on customer satisfaction at Mercure Serpong Alam Sutera Hotel and to determine the effect of facilities and service quality together on customer satisfaction at Mercure Serpong Alam Sutera Hotel. This study used a quantitative approach with the number of samples taken, which was 100. Quantitative methods consider human nature predictable from various facts such as ilmial, social, and measurable. Data sources were taken based on primary data and secondary data, it can be concluded that